The effect of intermittent hypobaric hypoxia on oxidative stress status and antioxidant enzymes activity in rat brain - Syarifah Dewi; Wawan Mulyawan; Septelia Inawati Wanandi; Mohamad Sadikin (Acta Biochimica Indonesiana, 2018)
Background: High altitude can cause hypobaric hypoxia (HH), resulted from the lower barometric pressure and hence partial pressure of oxygen. Hypoxia can lead to a lot of deleterious molecular and cellular changes, such as generation of free radicals or reactive oxygen species (ROS). Increasing of ROS can cause oxidative stress if the antioxidant enzyme does not increase simultaneously. Oxidative damage in brain has toxic effect on cognitive functions. Objective: In this study, we investigate effect of acute intermittent HH on oxidative stress and antioxidant enzyme activity in rat brain. Method: Wistar rats divided into 5 groups, consisting control group and four experimental groups which treated to HH. Rats were exposed to simulated HH equivalent to 35.000 feet in hypobaric chamber for 1 minute, repeated once a week. Results: Level of malondialdehyde and carbonyl in rat brain under acute HH increased at HH exposure (group I) compare to control group. These levels decreased afterward at intermittent HH exposure (group II-IV). Specific activity of superoxide dismutase (SOD) shows increasing level at intermittent HH exposure, especially group IV was increasing of SOD level significantly. The increasing pattern of specific activity of catalase was inversely from SOD pattern, but it still has higher activity in intermittent HH compare to control group. Conclusion: Brain tissue seems to be able to perform an adequate adaptive response to hypobaric hypoxia after the training, shown by its significantly decreased MDA and carbonyl level and also increased specific activity of SOD and catalase.